ANALYSIS OF THE GROWTH OF DIGITAL ENTREPRENEURSHIP STARTUP SOCIAL ENTERPRISE IN INDONESIA - Lestari, Eka Aprilia; Jesie, Titan Aprista; Sari, Amelia; Syefa, Bulan; Zaki, Ahmad (Universitas Muhammadiyah Tangerang, 2025)
Digital entrepreneurship has developed in various fields, one of which is social enterprise. This development can be seen from the growth of social enterprise startups in Indonesia ranging from creative industry, agriculture and fisheries, as well as education or education. This study aims to analyze the factors that influence the growth of social enterprise in Indonesia in the last five years, which has increased. Through the literature review method, this research explores information from various sources such as journals, the internet, and books relevant to the topic to understand the impact of digital technology on innovation in tackling social and environmental problems. This research was conducted by collecting data related to the topic raised in a study. The results of this study found that the factors that influence the development of social enterprises, such as the growth of digital technology and easy internet access, the development of digital funding and crowdfunding, public awareness of environmental sustainability, government and private sector support, and a culture of social care and cooperation.